PLGA confers upon conventional nonfluorescent molecules luminescent properties to trigger 1O2-induced pyroptosis and immune response in tumors - Lan Zou; Rujing Wang; Mengnan Zhao; Yuke Li; Chen Sun; Jinjin Xie; Yan Chen; Qian Jing; Dandan Mi; Sanjun Shi (Journal of Nanobiotechnology)
Abstract Pyroptosis, a recently identified cellular demise regulated by gasdermin family proteins, is emerging as a promising avenue in cancer immunotherapy. However, the realm of light-controlled pyroptosis in cancer cells remains largely unexplored. In this study, we took a deliberate approach devoid of any chemical alterations to develop a novel photosensitizer called “pharmaceutical-dots (pharm-dots)” by combining nonemissive polymers (Poly (lactic-co-glycolic acid), PLGA) with nonfluorescent invisible molecules like curcumin, berberine, oridonin into PLGA nanoparticles (PLGA-NPs). Initially, our research commenced with a comprehensive mechanistic comparison study, consolidating fragmented information on optical mechanisms. This exploration revealed that surface passivation atoms play a dominant role in governing the fluorescence emission of PLGA-NPs. Remarkably, these new luminophores, composed of two non-inherently luminous components, exhibit a remarkable synergistic boost in photoluminescence through a “0 + 0 > 2” phenomenon. In-depth investigations uncovered that these luminous PLGA-NPs, capable of generating 1O2, induce pyroptosis under photoexcitation conditions through the caspase-3/gasdermin E (GSDME) pathway. Simultaneously, our findings highlight PLGA-NPs as a novel optical formulation suitable for imaging, displaying substantial biological activity when paired with photoirradiation. This discovery holds the potential to facilitate the application of light-controlled pyroptosis in antitumor therapy, marking a promising stride toward innovative approaches in cancer treatment. Graphical abstract